Synchronized release of bufadienolides in a stable Lutrol F127 based solid dispersion prepared with spray congealing. (2nd November 2018) - Zuo, Wenbao; Li, Na; Zhao, Yue; Fu, Tingting; Fei, Wenling; Yu, Rui; Yang, Jianhong
Abstract: Objective: The objective of this study was to design and prepare a novel solid dispersion using spray congealing to achieve fast and synchronous dissolution of bufalin, cinobufagin, and resibufogenin, three therapeutically complementary drugs. Methods: The solid dispersion was characterized with dissolution, X-ray diffractometry, and fourier transform infrared spectroscopy after preparation and storage for four weeks at different temperatures and relative humidity. Results: It was found that all drugs were molecularly dispersed within matrix and had a significant enhancement (∼4-fold higher) of dissolution rate. Furthermore, synchronized release of different drugs from a single carrier was achieved due to the highly molecular dispersibility and the excellent solubilization properties of F127. In addition, the solid dispersion was physically stable for at least four weeks at controlled conditions. But for samples under stress conditions, the results showed that drug-rich phase was formed and storage temperature was the dominant factor in determining stability of the solid dispersion (SD). Conclusions: These findings highlight the fitness of spray congealing to co-deliver multiple drugs, which open new perspectives for the development of more advanced combination of multiple therapeutic agents, presumably improving the bioavailability and therapeutic efficacy.